Piston flow tubular type reactor optimal control system based on adaptive control grid - LIU XINGGAO; LI GUODONG (2018)
The invention discloses a piston flow tubular type reactor optimal control system based on an adaptive control grid; the system comprises a piston flow tubular type reactor body, and a liquid phase flowmeter and a temperature sensor, an analog-to-digital converter, a field bus network, a DCS and a main control room coolant flow velocity and reactor temperature display arranged on the piston flow tubular type reactor end, and a digital analog converter and a flow control valve arranged on the flow control valve end. The production process duration and coolant flow velocity control requirementsare assigned; the DCS obtains a flow velocity control strategy and converts same into an opening degree instruction of the flow control valve; the instruction is sent to the digital analog converter on the flow control valve end through the field bus grid, thus controlling the flow control valve to make corresponding motions according to the received control instruction; the liquid phase flowmeterand the temperature senso